Finite element ansysis and ISO calculation standard of tooth root bending strengthern of spiral beval gears - FENG Shaokun; WEI Bingyang; XIN Wen; CHENG Bo (Jixie qiangdu, 2025)
The calculation of bending strength for spiral bevel gears is complex, making accurate evaluation extremely challenging. Focusing on the two distinct calculation methods, B1 and B2, as outlined in the ISO 10300 standard, this study begins with the computational principles of both approaches. It compares the selection methods and numerical application principles for parameters involved in calculating root bending stress and allowable bending stress under both methods. The influence of parameter values on root bending stress calculations is analyzed for each method. Through computations on multiple design samples, the root bending stress values derived from both methods are compared. Finite element analysis is employed to validate the computational results. The findings indicate that due to differences in the types and values of correction coefficients used, there are certain discrepancies in the bending strength evaluation results obtained by the two methods. Method B1 yields a more conservative evaluation of root bending strength, with root bending stress approximately 5% lower than that calculated by Method B2. Although the ISO calculation standard accounts for load sharing among multiple teeth, it overlooks the combined effects on root bending stress, leading to deviations from finite element analysis results. Method B1 shows closer agreement with finite element results, with an error margin of about 6%.